Open system for energy services (OS4ES): An EU-funded research project to establish a non-discriminatory, multivendor-capability service delivery platform for smart grid services - Andreas Lang and Antonis Papanikolaou and Tim Dethlefs and Wolfgang Renz and Andrea Schroder and Jörg Benze (2015)
The Smart Grid is a paradigm shift towards a bidirectional energy and communication system relying on rich information exchange among all involved actors. Based on the experience of the participation in the CEN-CENELEC-ETSI Smart Grid Coordination Group (SG-CG) report creation1 for the EU-Mandate 490 \dqEuropean Smart Grid Standardization\dq [1], the EU-funded research project \dqOpen System for Energy Services (OS4ES)\dq was initiated. It will develop and prototype a generic, non-discriminatory, multivendor-capability ICT-platform for easy cross-linking of smart grid entities. It perceives no active market role, but supports market role owners with an easy to use middleware for bi-directional energy communication. This paper gives an overview about the methodology, architecture and functionality of the OS4ES research project.